Strategi Marketing PR TRON Dalam Meningkatkan Awareness Masyarakat Menuju Transportasi Angkutan Umum Online - Nefra Firdaus (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
ABSTRACT The development of increasingly sophisticated technology also influences changes in the development of transportation. Online transportation is currently a new business in Indonesia because the traffic jam opportunities that occur make online transportation an alternative for the community because it is more effective and efficient. There are several types of transportation that have long developed in Indonesia, such as Go-Jek, Uber, Grab and others. This condition raises competition among other online transportation companies as well as the displacement of conventional public transportation. This is what makes PT Teknologi Olah Rancang Nusantara (TRON) to make new innovations by changing conventional public transportation to online public transportation. TRON, an application-based transportation company with online transportation products, has changed the conventional way of transportation to be faster today. In introducing products to the public, different strategies from marketing public relations are needed to increase public awareness of the importance of minimizing the use of private vehicles to reduce congestion. The purpose of this paper is to discuss how TRON's strategy, especially in online transportation, involves all mediums, both offline and online, to get fast awareness from the Bekasi people. It is also interesting to analyze the interests of the community and the types of services that TRON offers. Keywords: Awareness; Marketing PR; Strategy; TRON